Non-liquid-injection lithium iron phosphate battery positive electrode repairing method based on deep-eutectic solvent stripping

The method employs a low-melting solvent mixture to separate and recover lithium iron phosphate battery positive electrode materials, overcoming the inefficiencies and environmental issues of current recycling techniques by achieving high-purity material recovery with reduced energy consumption and emissions.

CN119695324APending Publication Date: 2025-03-25NANJING NORMAL UNIVERSITY
View PDF 0 Cites 3 Cited by

Patent Information

Application Number
CN202411891764.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

Current methods for recycling defective lithium-ion batteries, particularly the positive electrode, face challenges such as high energy consumption and environmental pollution due to the production of harmful gases during high-temperature processing, and there is a need for efficient and environmentally friendly methods to recover valuable materials like lithium and aluminum from unsaled lithium-ion batteries.

Method used

A method utilizing a low-melting solvent mixture, primarily composed of ethylene glycol and metal chlorides, to selectively dissolve and separate the positive electrode materials and aluminum from unsaled lithium iron phosphate batteries, followed by chemical reprocessing to recover and regenerate the materials, reducing energy consumption and environmental impact.

Benefits of technology

This method effectively recovers high-purity positive electrode materials with minimal lithium loss, enabling efficient recycling and reuse, while avoiding high-temperature processing and reducing carbon emissions, thus addressing the limitations of existing technologies.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119695324A_ABST
    Figure CN119695324A_ABST
Patent Text Reader

Abstract

The invention discloses a non-liquid-injection lithium iron phosphate battery positive electrode repairing method based on deep eutectic solvent stripping, which comprises the following steps: preparing a deep eutectic solvent: putting a collected non-liquid-injection lithium iron phosphate battery positive electrode plate into ethylene glycol or the deep eutectic solvent for heating and soaking; according to the method, the positive electrode material and the aluminum foil can be effectively stripped, meanwhile, the lithium loss generated in the stripping process is reduced, the service life of the positive electrode material is prolonged, the service life of the positive electrode material is prolonged, the service life of the positive electrode material is prolonged, and the service life of the positive electrode material is prolonged. And finally, repairing and reusing the obtained positive electrode material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium battery recycling and processing, and in particular to a method for repairing a positive electrode of an unfilled lithium iron phosphate battery based on low eutectic solvent stripping. Background Art

[0002] In recent years, the sales of new energy vehicles have increased sharply under the promotion of national policies, and the output of lithium batteries has also gradually increased. In the production process, some products will have defects. If these defective lithium batteries continue to be produced and used, they will cause certain safety hazards, so they need to be processed, but direct disposal will cause waste lithium batteries to pollute the environment and waste resources. Since these unfilled lithium batteries have been collected by manufacturers in advance, they are convenient for centralized processing, and their models are the same, which is beneficial to the refined disassembly of the machines. At the same time, in the foreseeable future, the supply of battery raw materials such as cobalt and lithium will face serious shortages. In this context, it is of great practical significance to carry out research on harmless unfilled lithium battery processing and full resource recycling.

[0003] At present, the recycling of lithium batteries is mainly studied in the positive and negative active materials, among which the positive electrode has the greatest recycling value. The positive electrode sheet mainly includes positive electrode active materials, binders, conductive agents, current collectors, etc. It needs to be processed to remove the binder in order to better recycle the positive electrode active materials. The commonly used binder removal method is to effectively remove it through high-temperature decomposition, but high-temperature pyrolysis not only consumes a lot of energy but also produces fluorine-containing gases that cause environmental pollution. Therefore, the bonding effect between the binder polyvinylidene fluoride and the aluminum foil is destroyed by soaking in a low eutectic solvent, and finally the complete aluminum foil and sheet positive electrode material can be recycled.

[0004] Lithium battery solid phase repair technology can directly repair the positive electrode material and effectively restore the structure, composition and performance of the material. The positive electrode material of the unfilled lithium battery has a natural advantage in repair. It has almost no structural defects and can be directly reproduced with only a small amount of lithium replenishment or even no lithium replenishment. This reduces the demand for new resources and has important resource conservation significance. Summary of the invention

[0005] The purpose of the present invention is to provide a method for repairing the positive electrode of an unfilled lithium iron phosphate battery based on low eutectic solvent stripping to solve the problems raised in the above background technology. The method can effectively strip the positive electrode material and aluminum foil, while reducing the lithium loss generated during the stripping process, and finally repair and recycle the obtained positive electrode material.

[0006] To achieve the above object, the present invention provides the following technical solutions: The present invention provides a method for repairing a positive electrode of a non-liquid-injected lithium iron phosphate battery based on deep eutectic solvent stripping, comprising the following steps: Step 1: Using ethylene glycol as a hydrogen bond donor and a hydrogen bond acceptor in a certain proportion, heating and stirring to mix evenly to prepare a low eutectic solvent; Step 2: Collect the unfilled positive electrode sheet of the lithium iron phosphate battery, place the positive electrode sheet in the prepared low eutectic solvent or ethylene glycol solution, heat and soak it, and perform stirring, ultrasonic or oscillation treatment; sieve the low eutectic solvent from which the aluminum foil and the positive electrode sheet are peeled off through a sieve to obtain the aluminum foil and the liquid containing the positive electrode fragments, and separate the liquid by liquid-solid separation to obtain the positive electrode fragments and the reusable low eutectic solvent or ethylene glycol; Step 3: placing the positive electrode fragments obtained by liquid-solid separation in an organic solvent to soak and dissolve the binder therein, and obtaining positive electrode powder (containing acetylene black) and organic solvent filtrate by liquid-solid separation such as centrifugation and filter pressing; Step 4: Use organic solvent and deionized water to wash and dry the obtained positive electrode powder in turn; mix the obtained positive electrode lithium iron phosphate powder with the lithium source and additives and stir them evenly, react under certain conditions, and recover the reaction liquid through liquid-solid separation to obtain regenerated lithium iron phosphate powder and filtrate, and use pure additives and deionized water to wash and dry the obtained regenerated lithium iron phosphate powder in turn.

[0007] Furthermore, in step 1, the hydrogen bond acceptor is one or more of metal chlorides (such as zinc chloride, lead chloride, ferric chloride), quaternary ammonium salts (such as choline chloride, betaine), sodium carbonate, and urea, the molar ratio of ethylene glycol to the hydrogen bond acceptor is 10:1-2:1, and the temperature conditions for heating and stirring are 60-90°C.

[0008] Furthermore, in step 2, the immersion temperature in the ethylene glycol solvent is 80-120° C., and the immersion time is 1-3 h; the immersion temperature in the low eutectic solvent is 40-100° C., and the immersion time is 2 h.

[0009] Furthermore, in step three, the organic solvent is one or more of N-dimethylpyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide, and acetone.

[0010] Furthermore, in step three, the soaking temperature is 60-100° C., and the soaking time is 1-2 h; preferably, the soaking time is 90 min.

[0011] Furthermore, in step 4, the organic solvent is one or more of N-dimethylpyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide, and acetone.

[0012] Furthermore, in step 4, the lithium source is one or more of lithium iodide, lithium acetate, lithium acetylacetonate, and the additive is one or more of acetonitrile, ethanol, cyclohexane, methanol, dimethyl sulfoxide, and propylene glycol; the reaction temperature is 25-70° C., and the reaction time is 1-36 hours; Furthermore, in step 4, the molar ratio of the added lithium source and the positive electrode lithium iron phosphate powder is 1:50-1:100, and the solid-liquid ratio of the lithium iron phosphate powder to the additive is 1:20-1:50.

[0013] Compared with the prior art, the present invention has the following beneficial effects: In the present invention, the positive electrode material and the aluminum foil are stripped with the assistance of the low eutectic solvent, so that the complete aluminum foil and positive electrode fragments can be effectively recovered. There is no aluminum impurity in the positive electrode material, and high-temperature treatment is not required, which reduces energy consumption and carbon emissions.

[0014] The positive electrode fragments obtained by low eutectic solvent-assisted stripping in the present invention have high purity and complete structure, wherein the loss of lithium element is small, thus providing good conditions for subsequent recycling and treatment.

[0015] The present invention dissolves the binder polyvinylidene fluoride in the positive electrode fragments through an organic solvent, and can subsequently further recover the binder and regenerate the organic solvent, which is more economical.

[0016] The present invention uses chemical lithium replenishment technology to directly repair and regenerate the positive electrode material, thereby achieving effective recovery of the material's structure, components and performance. Compared with hydrometallurgy, it does not consume acid and alkali, is green and efficient, and can react under low temperature conditions, which is more energy-saving and safer than hydrothermal. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 Aluminum foil and positive electrode fragments obtained by stripping a non-liquid-injected lithium iron phosphate positive electrode sheet based on a low eutectic solvent; Figure 2 This is a schematic diagram of the present invention, which is based on the method of dissolving positive electrode fragments with an organic solvent and then centrifuging for liquid-solid separation to obtain positive electrode powder; Figure 3 It is a schematic flow chart of the method for repairing the positive electrode of a non-liquid-injected lithium iron phosphate battery based on low eutectic solvent stripping according to the present invention. DETAILED DESCRIPTION

[0018] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0019] like Figure 3 As shown, the present invention provides a technical solution: a method for repairing the positive electrode of an unfilled lithium iron phosphate battery based on low eutectic solvent stripping, comprising the following steps: Step 1: Using ethylene glycol as a hydrogen bond donor and a hydrogen bond acceptor in a certain proportion, heating and stirring to mix evenly to prepare a low eutectic solvent; Step 2: Collect the unfilled positive electrode sheet of the lithium iron phosphate battery, place the positive electrode sheet in the prepared low eutectic solvent or ethylene glycol solution, heat and soak it, and perform stirring, ultrasonic or oscillation treatment; sieve the low eutectic solvent from which the aluminum foil and the positive electrode sheet are peeled off through a sieve to obtain aluminum foil and a liquid containing positive electrode fragments, and separate the liquid into positive electrode fragments and reusable low eutectic solvent or ethylene glycol by liquid-solid separation; the aluminum foil and positive electrode fragments obtained by peeling off the low eutectic solvent are as follows: Figure 1 As shown; Step 3: Place the positive electrode fragments obtained by liquid-solid separation in an organic solvent to soak and dissolve the binder therein, and separate the liquid and solid by centrifugation, filter pressing, etc. to obtain positive electrode powder (containing acetylene black) and organic solvent filtrate; After the positive electrode fragments are dissolved by organic solvent and centrifugal liquid-solid separation, the positive electrode powder is as follows: Figure 2 As shown; Step 4: Use organic solvent and deionized water to wash and dry the obtained positive electrode powder in turn; mix the obtained positive electrode lithium iron phosphate powder with the lithium source and additives and stir them evenly, react under certain conditions, and recover the reaction liquid through liquid-solid separation to obtain regenerated lithium iron phosphate powder and filtrate, and use pure additives and deionized water to wash and dry the obtained regenerated lithium iron phosphate powder in turn. Example 1

[0020] The positive electrode sheets of the unfilled lithium battery are collected, and the positive electrode sheets are immersed in an ethylene glycol solvent at 90° C. for 2 hours; the ethylene glycol solvent from which the aluminum foil and the positive electrode sheet are peeled off is sieved through a 3-mesh sieve to obtain the aluminum foil and a mixture of the sheet-like positive electrode material and the ethylene glycol solvent, and the mixture is further filtered for liquid-solid separation to obtain the sheet-like positive electrode material and the ethylene glycol solvent respectively; The separated sheet positive electrode material was placed in dimethylformamide solvent and soaked at 60°C for 90 minutes to dissolve the remaining binder, and centrifuged at 8000r / min for 10 minutes to filter and separate the positive electrode lithium iron phosphate powder; the obtained lithium iron phosphate powder was washed and dried with dimethylformamide solvent and deionized water in turn; the lithium iron phosphate powder and aluminum foil were dissolved in aqua regia and ICP tested to determine their lithium element concentration, and the stripping efficiency of the positive electrode material was calculated to be 99.91%. The lithium element concentration was tested with a low eutectic solvent, and the lithium loss was calculated to be 0.27%.

[0021] Take 169.7 mg of lithium source material lithium iodide and 20 g of the obtained positive electrode lithium iron phosphate powder in a molar ratio of 1:100, add 1000 ml of acetonitrile solvent at a solid-liquid ratio of 1:50, stir at 300 r / min at 30°C for 20 hours, and separate the filtrate into regenerated lithium iron phosphate powder and filtrate. Use pure acetonitrile solvent and deionized water to wash the regenerated lithium iron phosphate powder, and dry it at 100°C for 1 hour.

[0022] The recycled lithium iron phosphate material and the binder polyvinylidene fluoride were mixed in a mass ratio of 9:1, and a proper amount of dimethyl pyrrolidone solvent was added to mix evenly. The slurry was evenly applied on aluminum foil, dried at 80°C, and finally assembled into a button battery. The charge and discharge cycle test was carried out at a rate of 0.1C, and the first charge specific capacity was 154.7mAh·g -1 , the discharge capacity is 153.6 mAh g -1 , the Coulomb efficiency is 99.3%. Example 2

[0023] Ethylene glycol and urea are mixed in a molar ratio of 10:1, stirred at 500 r / min for 1 hour at a temperature of 80°C to prepare a low eutectic solvent; the positive electrode sheets of the lithium battery that have not been injected with liquid are collected, and the positive electrode sheets are placed in the low eutectic solvent and immersed at 80°C for 2 hours; the low eutectic solvent from which the aluminum foil and the positive electrode sheet are peeled off is sieved through a 3-mesh sieve to obtain the aluminum foil and a mixture of the sheet positive electrode material and the low eutectic solvent, and further filtered to obtain the sheet positive electrode material and the low eutectic solvent respectively; The separated sheet positive electrode material was placed in a dimethylformamide solvent and soaked at 80°C for 90 minutes to dissolve the remaining binder, and then centrifuged at 8000r / min for 10 minutes to filter and separate the positive electrode lithium iron phosphate powder; the obtained lithium iron phosphate powder was washed and dried with dimethylformamide solvent and deionized water in turn; the lithium iron phosphate powder and aluminum foil were dissolved in aqua regia and ICP tested to determine their lithium element concentrations, and the stripping efficiency of the positive electrode material was calculated to be 99.73%. The low eutectic solvent was tested for its lithium element concentration, and the lithium loss was calculated to be 0.57%.

[0024] Take 212.1 mg of lithium source material lithium iodide and 20 g of the obtained positive electrode lithium iron phosphate powder in a molar ratio of 1:80, add 1000 ml of acetonitrile solvent at a solid-liquid ratio of 1:50, stir at 300 r / min at 30°C for 20 hours, and separate the filtrate into regenerated lithium iron phosphate powder and filtrate. Use pure acetonitrile solvent and deionized water to wash the regenerated lithium iron phosphate powder, and dry it at 100°C for 1 hour.

[0025] The recycled lithium iron phosphate material and the binder polyvinylidene fluoride were mixed in a mass ratio of 9:1, and a proper amount of dimethyl pyrrolidone solvent was added to mix evenly. The slurry was evenly applied on aluminum foil, dried at 80°C, and finally assembled into a button battery. The charge and discharge cycle test was carried out at a rate of 0.1C, and the first charge specific capacity was 156.8mAh·g -1 , the discharge capacity is 153.1mAh·g -1 , the Coulomb efficiency is 97.6%. Example 3

[0026] Ethylene glycol and sodium carbonate are mixed in a molar ratio of 20:1, stirred at 500 r / min for 1 hour at a temperature of 60°C to prepare a low eutectic solvent; the positive electrode sheets of the lithium battery that have not been injected with liquid are collected, and the positive electrode sheets are placed in the low eutectic solvent and immersed at 60°C for 2 hours; the low eutectic solvent from which the aluminum foil and the positive electrode sheet are peeled off is sieved through a 3-mesh sieve to obtain the aluminum foil and a mixture of the sheet positive electrode material and the low eutectic solvent, and further filtered to obtain the sheet positive electrode material and the low eutectic solvent respectively; The separated sheet positive electrode material was placed in dimethylacetamide solvent and soaked at 60°C for 90 minutes to dissolve the remaining binder, and centrifuged at 8000r / min for 10 minutes to filter and separate the positive electrode lithium iron phosphate powder; the obtained lithium iron phosphate powder was washed and dried with dimethylacetamide solvent and deionized water in turn; the lithium iron phosphate powder and aluminum foil were dissolved in aqua regia and ICP tested to determine their lithium element concentrations, and the stripping efficiency of the positive electrode material was calculated to be 99.68%. The low eutectic solvent was tested for its lithium element concentration, and the lithium loss was calculated to be 0.34%.

[0027] Take 169.7 mg of lithium source material lithium iodide and 20 g of the obtained positive electrode lithium iron phosphate powder in a molar ratio of 1:100, mix them, add 1000 ml of ethanol solvent at a solid-liquid ratio of 1:50, stir at 300 r / min at 30°C for 48 hours, and separate the filtrate into regenerated lithium iron phosphate powder and filtrate. Use pure ethanol solvent and deionized water to wash the regenerated lithium iron phosphate powder, and dry it at 100°C for 1 hour.

[0028] The recycled lithium iron phosphate material and the binder polyvinylidene fluoride were mixed in a mass ratio of 9:1, and a proper amount of dimethyl pyrrolidone solvent was added to mix evenly. The slurry was evenly applied on aluminum foil, dried at 80°C, and finally assembled into a button battery. The charge and discharge cycle test was carried out at a rate of 0.1C, and the first charge specific capacity was 151.5mAh·g -1 , the discharge capacity is 149.8 mAh g -1 , the Coulomb efficiency is 98.9%. Example 4

[0029] Ethylene glycol and sodium carbonate are mixed in a molar ratio of 10:1, stirred at 500 r / min for 1 hour at a temperature of 60°C to prepare a low eutectic solvent; the positive electrode sheets of the lithium battery that have not been injected with liquid are collected, and the positive electrode sheets are placed in the low eutectic solvent and immersed at 60°C for 2 hours; the low eutectic solvent from which the aluminum foil and the positive electrode sheet are peeled off is sieved through a 3-mesh sieve to obtain the aluminum foil and a mixture of the sheet positive electrode material and the low eutectic solvent, and further filtered to obtain the sheet positive electrode material and the low eutectic solvent respectively; The separated sheet positive electrode material was placed in dimethylacetamide solvent and soaked at 60°C for 90 minutes to dissolve the remaining binder, and centrifuged at 8000r / min for 10 minutes to filter and separate the positive electrode lithium iron phosphate powder; the obtained lithium iron phosphate powder was washed and dried with dimethylacetamide solvent and deionized water in turn; the lithium iron phosphate powder and aluminum foil were dissolved in aqua regia and ICP tested to determine their lithium element concentrations, and the stripping efficiency of the positive electrode material was calculated to be 99.87%. The low eutectic solvent was tested for its lithium element concentration, and the lithium loss was calculated to be 0.55%.

[0030] Take 83.7 mg of lithium source material lithium acetate and 20 g of the obtained positive electrode lithium iron phosphate powder in a molar ratio of 1:100, add 1000 ml of dimethyl sulfoxide solvent at a solid-liquid ratio of 1:50, stir at 70 ° C and 300 r / min for 24 hours, and separate the filtrate into regenerated lithium iron phosphate powder and filtrate. Use pure dimethyl sulfoxide solvent and deionized water to wash the regenerated lithium iron phosphate powder and dry it at 100 ° C for 1 hour.

[0031] The recycled lithium iron phosphate material and the binder polyvinylidene fluoride were mixed in a mass ratio of 9:1, and an appropriate amount of dimethyl pyrrolidone solvent was added to mix evenly. The slurry was evenly applied on aluminum foil, dried at 80°C, and finally assembled into a button battery. The charge and discharge cycle test was carried out at a rate of 0.1C. The first charge specific capacity was 146.3mAh·g-1, the discharge specific capacity was 143.9mAh·g-1, and the coulomb efficiency was 98.4%. Example 5

[0032] Ethylene glycol and sodium carbonate are mixed in a molar ratio of 2:1, stirred at 500 r / min for 1 hour at a temperature of 60°C to prepare a low eutectic solvent; the positive electrode sheets of the lithium battery that have not been injected with liquid are collected, and the positive electrode sheets are placed in the low eutectic solvent and immersed at 60°C for 2 hours; the low eutectic solvent from which the aluminum foil and the positive electrode sheet are peeled off is sieved through a 3-mesh sieve to obtain the aluminum foil and a mixture of the sheet positive electrode material and the low eutectic solvent, and further filtered to obtain the sheet positive electrode material and the low eutectic solvent respectively; The separated sheet positive electrode material was placed in dimethyl pyrrolidone solvent and soaked at 60°C for 90 minutes to dissolve the remaining binder, and centrifuged at 8000r / min for 10 minutes to filter and separate the positive electrode lithium iron phosphate powder; the obtained lithium iron phosphate powder was washed and dried with dimethyl pyrrolidone solvent and deionized water in turn; the lithium iron phosphate powder and aluminum foil were dissolved in aqua regia and ICP tested to determine their lithium element concentration, and the stripping efficiency of the positive electrode material was calculated to be 99.93%. The low eutectic solvent was tested for its lithium element concentration, and the lithium loss was calculated to be 0.82%.

[0033] Take 134.6 mg of lithium source material lithium acetylacetonate and 20 g of the obtained positive electrode lithium iron phosphate powder in a molar ratio of 1:100, add 1000 ml of methanol solvent at a solid-liquid ratio of 1:50, stir at 300 r / min at 30°C for 24 hours, and separate the filtrate into regenerated lithium iron phosphate powder and filtrate. Use pure methanol solvent and deionized water to wash the regenerated lithium iron phosphate powder and dry it at 100°C for 1 hour.

[0034] The recycled lithium iron phosphate material and the binder polyvinylidene fluoride were mixed in a mass ratio of 9:1, and a proper amount of dimethyl pyrrolidone solvent was added to mix evenly. The slurry was evenly applied on aluminum foil, dried at 80°C, and finally assembled into a button battery. The charge and discharge cycle test was carried out at a rate of 0.1C, and the first charge specific capacity was 142.9mAh·g -1 , the discharge capacity is 140.5 mAh g -1 , the Coulomb efficiency is 98.3%. Comparative Example 1

[0035] Citric acid and propylene glycol are mixed in a molar ratio of 3:2, stirred at 500 r / min for 1 h at a temperature of 50°C to prepare a low eutectic solvent, and the obtained low eutectic solvent is diluted with water to 1wt%; the positive electrode sheets of the lithium battery without liquid injection are collected, and the positive electrode sheets are placed in the low eutectic solvent and immersed at 20°C for 10 min; after the reaction is completed, the aluminum foil and the positive electrode material are filtered, washed, and dried to obtain the reusable low eutectic solvent; The positive electrode material and aluminum foil were dissolved in aqua regia and tested by ICP to determine their lithium concentrations. The stripping efficiency of the positive electrode material was calculated to be 99.9%. The lithium concentration of the low eutectic solvent prepared by citric acid and propylene glycol was tested, and the lithium loss was calculated to be 27.58%. Comparative Example 2

[0036] Instead of using ethylene glycol or a low eutectic solvent, the unfilled lithium battery positive electrode is soaked in deionized water.

[0037] The mixture was stirred at 500 r / min for 1 h at a temperature of 80° C. to prepare a low eutectic solvent; the positive electrode sheets of the lithium battery without liquid injection were collected, and the positive electrode sheets were immersed in deionized water at 80° C. for 2 h; the aluminum sheet and the positive electrode sheet were separated to obtain aluminum foil containing positive electrode materials and broken positive electrode sheets; The separated positive electrode fragments were placed in dimethylformamide solvent and soaked at 60°C for 90 minutes to dissolve the remaining binder, and centrifuged at 8000r / min for 10 minutes to filter and separate the positive electrode lithium iron phosphate powder; the obtained lithium iron phosphate powder was washed and dried with dimethylformamide solvent and deionized water in turn; the lithium iron phosphate powder and the aluminum foil containing the positive electrode material were dissolved in aqua regia and ICP tested to determine their lithium element concentrations, and the stripping efficiency of the positive electrode material was calculated to be 13.87%. The lithium element concentration of deionized water was tested, and the lithium loss was calculated to be 1.26%.

[0038] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0039] It should be noted that the above content merely illustrates the technical idea of ​​the present invention and cannot be used to limit the protection scope of the present invention. For ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications all fall within the protection scope of the claims of the present invention.

Claims

1. A method for repairing the positive electrode of an unfilled lithium iron phosphate battery based on deep eutectic solvent stripping, characterized in that: The following steps are involved: Step 1: Using ethylene glycol as a hydrogen bond donor, mixing with a hydrogen bond acceptor, and then heating and stirring to prepare a low eutectic solvent; Step 2: Collect the positive electrode sheets of the lithium iron phosphate battery that has not been injected with liquid, place the positive electrode sheets in an ethylene glycol solution or the low eutectic solvent prepared in step 1, heat and soak them, and perform stirring, ultrasonic or oscillation treatment, sieve through a sieve to obtain an aluminum foil and a liquid containing positive electrode fragments, and separate the liquid containing the positive electrode fragments by liquid-solid separation to obtain positive electrode fragments and a reusable low eutectic solvent or ethylene glycol solution; Step 3: placing the positive electrode fragments obtained in step 2 in an organic solvent to soak and dissolve the binder therein, and obtaining positive electrode powder and organic solvent filtrate by centrifugation and filtrate press for liquid-solid separation; Step 4: Use pure organic solvent and deionized water to wash and dry the obtained positive electrode powder in turn; mix the obtained positive electrode lithium iron phosphate powder with the lithium source and additives and stir them evenly to react, and recover the reaction liquid by liquid-solid separation to obtain regenerated lithium iron phosphate powder and filtrate, and use pure additives and deionized water to wash and dry the obtained regenerated lithium iron phosphate powder in turn.

2. According to claim 1, a method for repairing the positive electrode of a non-liquid-injected lithium iron phosphate battery based on deep eutectic solvent stripping is characterized in that: In step 1, the hydrogen bond acceptor is one or more of metal chloride, quaternary ammonium salt, sodium carbonate, sodium bicarbonate, ammonium carbonate and urea.

3. The method for repairing the positive electrode of a non-liquid-injected lithium iron phosphate battery based on deep eutectic solvent stripping according to claim 2, characterized in that: The metal chlorides include zinc chloride, lead chloride and ferric chloride, and the quaternary ammonium salts include choline chloride and betaine.

4. The method for repairing the positive electrode of a non-liquid-injected lithium iron phosphate battery based on deep eutectic solvent stripping according to claim 1, characterized in that: In step 1, the molar ratio of ethylene glycol to hydrogen bond acceptor is 20:1-2:1, and the mixture is heated to 60-90° C. and stirred evenly to prepare a low eutectic solvent.

5. The method for repairing the positive electrode of a non-liquid-injected lithium iron phosphate battery based on deep eutectic solvent stripping according to claim 1, characterized in that: In step 2, the immersion temperature in the ethylene glycol solution is 80-120° C., and the immersion time is 1-3 hours. The immersion temperature in the low eutectic solvent is 40-100° C., and the immersion time is 2 hours.

6. The method for repairing the positive electrode of a non-liquid-injected lithium iron phosphate battery based on deep eutectic solvent stripping according to claim 1, characterized in that: In step three, the organic solvent is one or more of N-dimethylpyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide, and acetone.

7. The method for repairing the positive electrode of a non-liquid-injected lithium iron phosphate battery based on deep eutectic solvent stripping according to claim 1, characterized in that: In step three, the soaking temperature is 60-100° C. and the soaking time is 1-2 h.

8. The method for repairing the positive electrode of a non-liquid-injected lithium iron phosphate battery based on deep eutectic solvent stripping according to claim 1, characterized in that: In step 4, the organic solvent is one or more of N-dimethylpyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide, and acetone; the lithium source is one or more of lithium iodide, lithium acetate, and lithium acetylacetonate; and the additive is one or more of acetonitrile, ethanol, cyclohexane, methanol, dimethyl sulfoxide, and propylene glycol.

9. A method for repairing the positive electrode of a non-liquid-injected lithium iron phosphate battery based on deep eutectic solvent stripping according to claim 1, characterized in that: In step 4, the molar ratio of the added lithium source and the positive electrode lithium iron phosphate powder is 1:50-1:100, and the solid-liquid ratio of the lithium iron phosphate powder to the additive is 1:20-1:

50.

10. A method for repairing the positive electrode of a non-liquid-injected lithium iron phosphate battery based on deep eutectic solvent stripping according to claim 1, characterized in that: In step 4, the reaction temperature is 25-70°C and the reaction time is 16-48h.

Citation Information

Cited By

  • Device and method for continuously separating positive electrode powder and aluminum foil of lithium battery in situ

    CN115764040A

  • Green stripping and recycling method for positive electrode material of waste lithium iron phosphate battery

    CN120280594A

  • A green stripping and recycling method for waste lithium iron phosphate battery positive electrode materials

    CN120280594B